Note that if the exponential function is in the form `f(x)= a ^x + c` , the horizontal asymptote is `y = c` .

**Hence, the horizontal asymptote of the function `y = e^x - 1` is `y=-1` .**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now